Unintended Consequences: How Veterans Under the G.I. Bill Influence UWEC - Osborn, Scotty (My University, 2008)
In 1944, Congress passed the Servicemen’s Readjustment Act to give returning WWII soldiers special benefits for their service. The original intent of the G.I. Bill was to provide economic relief to the veterans until they could obtain a job. Unrealized at the time, the G.I. Bill’s most important component would be the educational benefits that it provided for veterans. The Bill paid for the veterans’ tuition to go to any college throughout the country. The veterans eagerly enrolled in college to obtain an education that could allow them to get a better job. The enrollment of these veterans provided tremendous relief to the colleges that were struggling during the war years, and they influenced the direction that higher education would take. This paper will specifically focus on the impact and influence that veterans had on the University of Wisconsin – Eau Claire, then the Eau Claire State Teachers College. From 1945-1950 the veterans shaped the direction of the college by the demands that they made. This would influence the college for years afterwards.
Keywords: G.I. Bill--Educational aspects.; United States. Servicemen's Readjustment Act of 1944.; Eau Claire State Teachers College.; Veterans--Education--Wisconsin--Eau Claire.; Veterans--Education--Law and legislation--United States.